Nawiązka z art. 46 § 2 k.k. orzekana zamiast obowiązku naprawienia szkody - Muszyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The article includes an assessment of the legal regulation of exemplary damages from Article 46 § 2 of the Criminal Code imposed instead of remedying damage obligation. After covering the legal prerequisites of exemplary damages adjudication, the author indicates interpretation doubts arising on its background. The author also makes an attempt to answer the question whether exemplary damages from Article 46 § 2 of the Criminal Code pursue compensational objective and what their actual role is.
Keywords: nawiązka; naprawienie szkody; odszkodowanie; przestępstwo